2023
DOI: 10.3390/cells12162117
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Engineering for Interrogating the Ubiquitin–Proteasome System and Novel Therapeutic Strategies

Jason Q. Tang,
Mary M. Marchand,
Gianluca Veggiani

Abstract: Protein turnover, a highly regulated process governed by the ubiquitin–proteasome system (UPS), is essential for maintaining cellular homeostasis. Dysregulation of the UPS has been implicated in various diseases, including viral infections and cancer, making the proteins in the UPS attractive targets for therapeutic intervention. However, the functional and structural redundancies of UPS enzymes present challenges in identifying precise drug targets and achieving target selectivity. Consequently, only 26S prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Following the same line of evidence, the exploitation of engineered ubiquitin variants (UbVs) will pave the way to improve target specificity and selectivity. In fact, in the last few years, several studies have demonstrated that UbVs that tightly bind to UPS–related enzymes (such as E2s, E3s, and DUBs) may serve as valuable tools to modulate the function of these enzymes [ 156 ], as exemplified by the UbVs which inhibit USP7 and USP2a deubiquitinases described in Section 6.1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the same line of evidence, the exploitation of engineered ubiquitin variants (UbVs) will pave the way to improve target specificity and selectivity. In fact, in the last few years, several studies have demonstrated that UbVs that tightly bind to UPS–related enzymes (such as E2s, E3s, and DUBs) may serve as valuable tools to modulate the function of these enzymes [ 156 ], as exemplified by the UbVs which inhibit USP7 and USP2a deubiquitinases described in Section 6.1 .…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of this strategy relies on several properties, including the presence of Ub-binding sites in the UPS proteins, the ability of Ub to engage in low-affinity but specific interactions with UPS components and the possibility of genetically engineering the ubiquitin molecules. Over the past few years, UbVs have been obtained and screened against multiple components of UPS, such as E2 conjugating enzymes, E3 ligases and DUBs [ 156 ]. UbVs show high affinity and selectivity in targeting specific UPS protein and they can act as inhibitors, activators or modulators of targeted proteins.…”
Section: Developing Strategies To Target Ubiquitination In Cancer The...mentioning
confidence: 99%
See 1 more Smart Citation